Up-regulated RxLR effector genes of Plasmopara viticola in synchronized host-free stages and infected leaves of hosts with different susceptibility. Issue 12 (December 2018) - Gómez-Zeledón, Javier; Spring, Otmar
Abstract: Fast recognition of host signals and early activation of infection mechanisms in Plasmopara viticola are decisive for successful infestation of Vitis vinifera . To better understand interactive processes at the first front line of combat between the pathogen and its host, a specific pre-infective stage was generated in a host-free system. Zoospore encystment was triggered within minutes after treatment with CaCl2 . Subsequently, high rates of germ tube formation occurred in a synchronized manner. This method was employed to compare development-related gene expression in strains of different virulence. Soon after germination, spores showed strong up-regulation of two effector genes, PvRxLR18 and PvRxLR28, particularly in the high virulence strain. On infected grapevine leaf-discs of cultivars with different susceptibility, a similar up-regulation was found at 6 hours post inoculation (hpi). This effect was much more evident in the high virulence than in the low virulence strain and was significantly higher on leaves of the tolerant cultivar Regent than on Müller-Thurgau. In addition, PvRxLR67 was up-regulated 24 hpi in the high virulence strain indicating that different effectors are active in later infection stages. Differences in the expression pattern of RxLR effector genes between the two strains corroborated with infection symptoms visible by sporulation.